'We Lost on the Numbers, But for Us It's a Victory': New Caledonia's 2018 Referendum on Self-Determination. Issue 2 (3rd April 2019) - Maclellan, Nic
ABSTRACT: On 4 November 2018, more than 141, 000 voters in New Caledonia went to the polls to determine the political status of the French Pacific dependency. A referendum on self-determination, the culmination of a 20-year transition under the 1998 Noumea Accord, posed the question: 'Do you want New Caledonia to accede to full sovereignty and become independent?' In an unprecedented turnout, 56.67 per cent of voters decided to remain within the French Republic, while 43.33 per cent voted Yes for independence. These figures, with a clear majority opposing full sovereignty, suggest a setback for New Caledonia's independence coalition Front de Libération Nationale Kanak et Socialiste (FLNKS). In reality, the size of the Yes vote has disappointed partisans of the French Republic and opened the way for a second referendum in 2020. After briefly outlining the 1998 Noumea Accord, the article details the results and participation rates in the November 2018 vote. It then focuses on different aspects of the referendum campaign, including: the role of opinion polling, administration of the referendum by the French state; disputes over electoral registration; international monitoring; key objectives of the anti-independence parties; grassroots campaigning by the FLNKS and the significance of the youth vote. It flags some issues in the aftermath of the referendum, as New Caledonians prepare for the next local elections to be held on 12 May 2019.